1988
DOI: 10.1007/bf00405665
|View full text |Cite
|
Sign up to set email alerts
|

Work at sea: a study of sleep, and of circadian rhythms in physiological and psychological functions, in watchkeepers on merchant vessels

Abstract: The safety of a ship depends substantially on its bridge watchkeepers, whose alertness and efficiency must be maintained at all hours of the day and night. Fatigue, circadian rhythms, and sleep disruption occasioned by the unusual working hours of these personnel may all affect their performance. A methodology for assessing the magnitude of this problem is proposed. The application of this methodology in a large-scale shipboard study of merchant mariners on extended voyages is then described, and details given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Almost all seamen work in 8 h shift: four hours in watch keeping and eighthour rest, or 6 h shift: six hours in watch keeping and rest. An exception is the captain seamen who don't have watch keeping and are normally engaged in daywork 6,7) . On trading vessels the captain has to be awake to work, and deal with whatever happens during the night 8) .…”
Section: Discussionmentioning
confidence: 99%
“…Almost all seamen work in 8 h shift: four hours in watch keeping and eighthour rest, or 6 h shift: six hours in watch keeping and rest. An exception is the captain seamen who don't have watch keeping and are normally engaged in daywork 6,7) . On trading vessels the captain has to be awake to work, and deal with whatever happens during the night 8) .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that time-related PSFs such as suddenness of onset, time available, and task criticality all happened in more than one third of the accidents. This suggests that there is a difference between navigation on small naval vessels and large merchant ships, where monitoring constitutes a larger part of the task (Colquhoun et al, 1988).…”
Section: Psfsmentioning
confidence: 99%
“…We can observe the adoption of the following approaches: self-report measures [24], measures of physiological processes, a combination of physiological, behavioural and self-report measures [25].…”
Section: The Fatigue Factor In the Human Resources Management On Boarmentioning
confidence: 99%
“…The main cause identified for fatigue of seafarers is related to the sleep patterns, that is the quality and quantity of sleep [25]. More specifically some authors have identified some key features related to fatigue that impact on the quality and quantity of sleep, such as fragmented (and therefore poorer quality) sleep, having to sleep at physiologically inappropriate times, insufficient breaks for resting between shifts, long work days, and so on [26].…”
Section: The Fatigue Factor In the Human Resources Management On Boarmentioning
confidence: 99%